The problem of energy crisis in Peru: oil contracts, petroleum prices and related topics - Giesecke, Carlos R. (1985)
This article has the dual purpose of explaining the nature of the energy crisis in Peru and of contributing towards placing the actual debate on this matter in perspective. To that effect, the author proposes the use of three basic principies in the fleld of energy economics which, according to his judgment, are essential both for the study of the problem as well as for establishing rational criterio for the decision making process. In the light of such principies, the problem-crisis of oil reserves is examined and the succesive stages needed to reach a solution are analyzed. So, answers are sought for questions such as: should domestic production be geared to domestic energy demand or to the needs to generate foreign exchange?, what are the ways and conditions that should norm the process of oil extraction, i.e., how should the revenues generated by the production of oil be distributed between the State and foreign capital? Lastly, the author comments on the use of diesel in the generation of hydrotermal electricity and calis for its replacement with more abundant and less expensive materials such as heavy oil or coal.​